2023
DOI: 10.1021/acs.inorgchem.3c02043
|View full text |Cite
|
Sign up to set email alerts
|

Changing Directions: Influence of Ligand Electronics on the Directionality and Kinetics of Photoinduced Charge Transfer in Cu(I)Diimine Complexes

Lei Wang,
Zhu-Lin Xie,
Brian T. Phelan
et al.

Abstract: A key challenge to the effective utilization of solar energy is to promote efficient photoinduced charge transfer, specifically avoiding unproductive, circuitous electron-transfer pathways and optimizing the kinetics of charge separation and recombination. We hypothesize that one way to address this challenge is to develop a fundamental understanding of how to initiate and control directional photoinduced charge transfer, particularly for earth-abundant first-row transition-metal coordination complexes, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…These findings collectively indicate that the strong electron withdrawing ability of R can both enhance the ISC processes from S 1 (JT) to T 1 states by reducing their energy gap, thereby further accelerating the recovery dynamics of the ground state (S 0 ) from the T 1 state. Indeed, a very recent study by K. Mulfort and co-workers has reported a similar observation regarding the longest lifetime constant τ 3 for the relaxation of T 1 to S 0 states in their OTA investigation of [Cu­(N^N) 2 ] + complexes, including the ligand substituents with the variable electron donating or withdrawing ability . Their findings also indicated that a strong electron-withdrawing ability of the ligand substituent can significantly shorten τ 3 .…”
supporting
confidence: 55%
See 1 more Smart Citation
“…These findings collectively indicate that the strong electron withdrawing ability of R can both enhance the ISC processes from S 1 (JT) to T 1 states by reducing their energy gap, thereby further accelerating the recovery dynamics of the ground state (S 0 ) from the T 1 state. Indeed, a very recent study by K. Mulfort and co-workers has reported a similar observation regarding the longest lifetime constant τ 3 for the relaxation of T 1 to S 0 states in their OTA investigation of [Cu­(N^N) 2 ] + complexes, including the ligand substituents with the variable electron donating or withdrawing ability . Their findings also indicated that a strong electron-withdrawing ability of the ligand substituent can significantly shorten τ 3 .…”
supporting
confidence: 55%
“…In particular, knowledge about their photoexcited electronic and structural dynamics is essential for advancing the facile development of heteroleptic Cu­(I) complex photosensitizers. Drawing from the insights gained in recent studies of Cu­(I) complexes, where it has been demonstrated that the photoexcited properties can be finely tuned by steric and electronic effects via meta and para substitutions on the ligands, we have here synthetically developed a novel series of prototype heteroleptic Cu­(I) complexes by employing a meta -substituted (i.e., 5,5′-substituted) 2,2′-bipyridyl ligand ([Cu­(PPh 3 ) 2 (BPy R )] + , depicted in Scheme ). The meta -position of the 2,2′-bipyridyl ligand was modified with nonbulky functional groups (R= CH 3 (Me) ( 1 ), H ( 2 ), Br ( 3 ), or COOCH 3 (COOMe) ( 4 ), see Scheme ), which are expected to exhibit an increasing electron-withdrawing nature but negligible steric effect.…”
mentioning
confidence: 99%
“…Charge transfer switches directions for all molecules when observing the predominant molecular orbitals, contributing to higher energy orbitals for the S 0 → S 3 transition shown in Figure . This molecular design emulates similar principles to a recent publication from Mulfort and co-workers, who also controlled the direction of charge transfer in Cu­(I) HETPHENs using 4,7-substituents in the secondary ligand …”
Section: Resultsmentioning
confidence: 60%
“…The combined static and dynamic absorption and 77 K photoluminescence (PL) experiments support the finding of the molecular orbital calculations, which favor MLCT excitation being directed toward the secondary ligands in 2 – 4 . Work concurrently performed and recently published by Mulfort and co-workers explored a conceptually similar ligand motif; rather than placing arylethynyl at the 4,7-positions, they employed an array of substituents with various Hammett parameters in identical positions . This work demonstrates a similar profound influence that arylethynyl units impart on the optical and electrochemical characteristics of Cu­(I) HETPHEN complexes, evidenced through enhanced broadband light absorption properties and tuned redox potentials.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation